Pragmatic Web as a Service Provider for the Internet of Things - Purnomo, Bambang (IEEE, 2014)
In this paper, we present the Pragmatic Web architecture and how it can be used to improve automation for the Internet of Things. Pragmatic Web system is the next advancement on the Web, where the application provides context dependent data and services, hence improves its usefulness for service consumers. We argue that the Pragmatic Web is a good match for the Internet of Things, especially for home automation which involves service requests to the Web. Our contributions in this paper are software architecture of the Pragmatic Web and how the interaction between the Pragmatic Web and smart device can be implemented: (1) three-phase of interaction mechanism, and (2) an improvement of FIPA ACL message and message content for communication. Our contributions will enable Web developers to develop Web applications that provide context dependent data and services for the Internet of Things or any other software agents. To this end, an E-Commerce scenario is presented.